White Mustard (Sinapis alba L.) Oil in Biodiesel Production: A Review - Mitrović, Petar M.; Stamenković, Olivera S.; Banković-Ilić, Ivana; Djalović, Ivica G.; Nježić, Zvonko B.; Farooq, Muhammad; Siddique, Kadambot H. M.; Veljković, Vlada B. (Frontiers in Plant Science, 2020)
White mustard (Sinapis alba L.) seed oil is used for cooking, food preservation, body and hair revitalization, biodiesel production, and as a diesel fuel additive and alternative biofuel. This review focuses on biodiesel production from white mustard seed oil as a feedstock. The review starts by outlining the botany and cultivation of white mustard plants, seed harvest, drying and storage, and seed oil composition and properties. This is followed by white mustard seed pretreatments (shelling, preheating, and grinding) and processing techniques for oil recovery (pressing, solvent extraction, and steam distillation) from whole seeds, ground seed or kernels, and press cake. Novel technologies, such as aqueous, enzyme-assisted aqueous, supercritical CO2, and ultrasound-assisted solvent extraction, are also discussed. The main part of the review considers biodiesel production from white mustard seed oil, including fuel properties and performance. The economic, environmental, social, and human health risk/toxicological impacts of white mustard-based biodiesel production and use are also discussed.